(untitled) (Sport and Exercise Psychology, 2025)
Ski mountaineering is a discipline that combines physical endurance, risk management, and mental adaptation in extreme environments. With its recent inclusion among the Olympic disciplines, this sport is gaining increasing attention not only for its technical challenges but also for the mental training strategies used by athletes to enhance performance and safety. This article explores key psychological techniques, such as mental imagery, positive self-talk, emotional regulation, and fear management, highlighting their role in improving resilience and decision-making under pressure. Additionally, the article discusses the gap in scientific research on mental preparation in ski mountaineers, calling for greater academic interest in this field. Understanding and implementing effective mental training strategies could not only optimize athletes’ performance but also contribute to injury prevention and psychological well-being.